(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A graceful labeling of a tree T with n edges is a bijection f : V(T) {0,1,2, … n} such that {|f(u)-f(v)| : uv E(T)} equal to {1,2,3,…,n}. A spider graph is a tree with one vertex of degree at least 3 and all others with degree at most 2. We show that some classes of spider graphs admit graceful labeling.